Hard drug in self-medication practices: A qualitative study - Zulrahamatulhuda, Zulrahamatulhuda; saimi, saimi; Khalik, Lalu Abdul (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Self-medication is an act of self-medication without medical consultation, the practice of self-medication in the people of West Nusa Tenggara reaches 66.62% and the community in Bima City is indicated to be 60.44%. This practice risks causing serious side effects and drug resistance. Purpose: To explore why the practice of hard drug self-medication is high in the community of Bima City. Method: Employing a descriptive qualitative approach with an emphasis on exploratory research. Conducted in Bima City starting in August 2024, it involved a total sampling method, selecting 10 participants who served as key informants from the National Agency of Drug and Food Control. Data collection was carried out through triangulation, integrating multiple sources, methods, and theories to enhance result validity. In-depth interviews were used as the primary data collection technique, and the data were analyzed using thematic analysis to extract key insights and interpret the underlying meaning of the findings. Results: Self-medication practices, such as buying antibiotics without a prescription, risk causing drug resistance and side effects. Monitoring drug distribution, especially online purchases, is a challenge for the Health Office and National Agency of Drug and Food Control. People choose practical and cost-effective ways, while pharmacists face pressure in selling drugs without a prescription. Collaboration and education are needed to ensure safe and rational drug use. Conclusion: The high cost of medicine and queues at health facilities encourage self-medication, exacerbated by poor Social Security Administration services. 24-hour pharmacies and online purchasing make it easier to access drugs without a prescription, with weak distribution oversight. Lack of accurate information and distrust of formal health services increase the risk of side effects and drug abuse.